Pembangunan Aplikasi Android Rekomendasi Tempat Rental Motor Di Kota Malang Dengan Metode AHP TOPSIS Berbasis Location Based Services - Jeriko Hosea Julanto; Komang Candra Brata; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
There are very few native townspeople of Malang City, who know the motorcycle rental in Malang City. In fact, as already know, the city of Malang is a tourist city which is always crowded by visitors. Plus each person has different criteria in choosing a motorcycle rental. Scratch facilities make users have difficulty in choosing a motorcycle rental in Malang City. To solve these problems required decision support system (DSS) to support and facilitate the user in choosing a motorcycle rental. The DSS method must have a low time complexity. Application android recommendation of motorcycle rental in malang city by AHP TOPSIS method based on location based services is an application that gives recommendation of motorcycle rental in malang city according to weight of interest criteria entered by user. These criteria include the price of 125cc motorcycle rental per day, the location of the motorcycle rental, the popularity and rating of the motorcycle rental. Tests of this research resulted that the percentage of usability reached the value of 82.82%, where this value is included in good category, then the functional test result is 100%, then the conformity test also stated that this application has 90% test result value.